How to win (reviewer) friends and influence (editorial) people - Thomson, William M. (Journal of Dentistry Indonesia, 2019)
While collecting the right data and conducting the appropriate analyses is critical to scientific success, writing up your findings and steering them through submission, peer review and into print is at least as important. If you don’t publish your work, your scientific career is likely to be brief and unrewarding. Thus, technical writing is a key skill for any researcher. In this paper, the author goes through the hard lessons learned from nearly three decades of experience as a scientist, reviewer and (latterly) editor. He covers such topics as precision in technical writing, common errors in presenting and describing data, writing a Discussion section, and dealing with reviewers and editors.